2016
DOI: 10.1111/resp.12918
|View full text |Cite
|
Sign up to set email alerts
|

Lung function in patients with lung injury due to household chemical inhalation: Post hoc analysis of a prospective nationwide cohort

Abstract: Half of the patients with inhalation injury exhibited stabilization of lung function within several years of onset. However, lung function was impaired in the remaining patients. This impairment associated with lung function at onset and exposure intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…Notably, peripheral airway dysfunction in X5 and AX was not related to bronchodilator response in the present study. These results are compatible with prior publications’ results on HDLI addressing small airway involvement on computed tomography (CT) and a restrictive pattern on spirometry in adults [13, 42]. In addition, a previous study showed that bronchiolar destruction and a centrilobular distribution of alveolar destruction following HD exposure were documented by lung biopsy [9].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Notably, peripheral airway dysfunction in X5 and AX was not related to bronchodilator response in the present study. These results are compatible with prior publications’ results on HDLI addressing small airway involvement on computed tomography (CT) and a restrictive pattern on spirometry in adults [13, 42]. In addition, a previous study showed that bronchiolar destruction and a centrilobular distribution of alveolar destruction following HD exposure were documented by lung biopsy [9].…”
Section: Discussionsupporting
confidence: 92%
“…However, adult cases of all HDLI, regardless of the strand of HD, had only a restrictive pattern on spirometry [13, 42]. Restrictive lung diseases will result in a decrease in reactance because the elastic recoil, and therefore the ability of the lung parenchyma to reflect the signal back, will be decreased [29].…”
Section: Discussionmentioning
confidence: 99%
“…Many chemical airborne exposures are associated with a decrement in lung function in adults, including in cases of large man-made disasters, such as the 1984 Bhopal Union Carbide methyl isocyanate gas release, the 2005 chlorine gas release from the Graniteville train accident, and current 2006 epidemic HD exposure (Additional file 1: Table S1). HD inhalation causing HDLI has been found to be characterized by restrictive lung defect in adults [10, 11]. Despite the associations observed in HDLI adults, the potential effects and the long-term consequences of HDLI children on lung function have not been explored, although children’s lungs are more susceptible to airborne exposures than those of adults [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with drug‐induced acute lung injury, BAL thrombomodulin levels were independently predictive of respiratory failure, while inhibition of neutrophil elastase and chemotaxis was beneficial in acute respiratory distress syndrome (ARDS) in humans and in a mouse model, respectively . Acute lung injury following household chemical inhalation was associated with a permanent restrictive defect in half of the patients …”
Section: Interstitial Lung Diseasementioning
confidence: 99%